THE EFFECTIVENESS OF TRAINING TOWARDS JOB SATISFACTION WITH JOB PERFORMANCE AS A MEDIATING VARIABLE AT AGRICULTURAL AGENCY: EVIDENCE FROM MALAYSIA - Nurul Muniroh Basir; Sentot Imam Wahjono (UMSurabaya Publishing, 2014)
The aim of this research is to study the effectiveness of training towards job satisfaction with job performance as mediating variable. This research conducted by Qualitative approach with Path Analysis. The population of this research are 1,597 employees in Muda Agricultural Development Authority (MADA), Kedah, Malaysia. 310 sets of questionnaires distributed to respondents and 222 are collected back for analysis with SPSS. This research found that Job Satisfaction influence by Training directly or through by Job Performance, but better through by. These research findings have theoretical implications that the effectiveness og the employee’s job performance after training should be through the achievement of job satisfaction first.Training, job performance, job satisfaction, Muda Agricultural Development Authority (MADA) Malaysia.Structure, Growth Rate, Profitability, Cash Flow and Firm Size